Level of acceptance towards consumer in the shariah compliance hotel in Kota Bharu, Kelantan - Mansor, Rohana; Bachan Singh, Sarguna; Yamin, Sharifah; Mohamad Rodzi, Shuhaida (2015)
Halal hub is a concerted effort among the Islamic countries such as Halal food, halal manufactures, halal pharmaceuticals, halal cosmetic, halal packaging, halal logistic product as well as halal services from all over the world. In fact, it has been a goal of a the Malaysia as an Islamic country and being seriously on establishing a Halal hub for the product as well as services in finance and tourism. Due to an interesting development of the Shariah Compliance Hotel, it is very pertinent to illustrate several features and the characteristic of hospitality services which comes within the Islamic context which universally accepted and tailoring with the tourist packages especially to accommodate the needs of the upcoming boom of Muslim travelers and vacationers from the Middle East West Asia and other Islamic countries. Using the example of Malaysia as a case study, this paper will also illustrate the opportunities which arise in delivering of such concept of the so-called an Islamic hotel brands. Apart from that, the barriers and challenges that might be faced by the hospitality industries in developing the Shariah Compliance Hotel in Malaysia are then discussed and identified. The study will be conducted using qualitative research in which data is collected through library research and session of interviews with the relevant authorities. It is hopeful that finding of this paper can provide information to the authoritative body and to industry players as well. The result of this paper will also indicate the importance for the hoteliers to have knowledge and fully prepared with the opportunities and challenges that they might be facing prior developing the Shariah Compliance Hotel in Malaysia.